Workshop Penggunaan Media Sosial sebagai Sarana Promosi Sekolah - Muamar Al-Qodri; Satria Wiguna; Hafizh Hafizh (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
In today’s digital era, many schools face challenges in utilizing social media as an effective means for promotion and enhancing the image of the institution. Despite the enormous potential of social media, many educators and administrative staff are still lacking in skills in optimally managing this platform. Based on these problems, the purpose of this study was to improve the skills and understanding of participants regarding the use of social media as a strategic promotional tool for schools, as well as to encourage the adoption of more effective digital marketing practices. The method used in this study was a participatory approach through an interactive workshop. The workshop involved hands-on training sessions, group discussions, and social media content creation simulations, which were designed to provide practical experience and enhance participants’ understanding directly. Data were collected through observation, pre- and post-workshop questionnaires, and interviews with participants to measure changes in their skills and perceptions. The results showed a significant increase in participants’ technical skills in managing social media, as well as a positive change in their perspectives on the importance of social media as a promotional tool. Most participants reported that they felt more confident and ready to implement more structured and data-driven promotional strategies in their schools. These results indicate that the workshop successfully achieved its objectives and had a positive impact on participants’ ability to utilize social media effectively.